2017
DOI: 10.1123/pes.2016-0048
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cardiorespiratory Fitness and Overweight With Academic Performance in 12-Year-Old Brazilian Children

Abstract: The results highlight the importance of maintaining high fitness levels in girls throughout adolescence a period commonly associated with reductions in physical activity levels and CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…The result regarding a significant association between CRF and academic performance in male college first-year students was the same as the other studies, which examined the same two variables in children (De Almeida Santana et al, 2017) and adolescents (García-Hermoso, Esteban-Cornejo, Olloquequi, & Ramírez-Vélez, 2017;Kwak et al, 2009). In addition, the CRF was the main explanatory factor for the GPA in male college participants after further regression.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The result regarding a significant association between CRF and academic performance in male college first-year students was the same as the other studies, which examined the same two variables in children (De Almeida Santana et al, 2017) and adolescents (García-Hermoso, Esteban-Cornejo, Olloquequi, & Ramírez-Vélez, 2017;Kwak et al, 2009). In addition, the CRF was the main explanatory factor for the GPA in male college participants after further regression.…”
Section: Discussionsupporting
confidence: 81%
“…There were several possible factors for the improvement of cognition due to the intervention of exercise, such as an increase in cortical thickness (Reiter et al, 2015), maintenance or improvement of brain function and structure (Burzynska et al, 2014;Colcombe et al, 2006), and an increase in brain blood flow (Burdette et al, 2010) although further studies are warranted for precise mechanisms. Recent studies indicated (De Almeida Santana et al, 2017;García-Hermoso, Esteban-Cornejo, Olloquequi, & Ramírez-Vélez, 2017) that CRF was significantly related with academic performance in children and young teenagers.…”
Section: Introductionmentioning
confidence: 99%
“…This positive correlation is also presented in other studies in children and adolescents where higher CRF was related to increased mean academic attainment in both boys and girls [39,40]. Nevertheless, in a study in Brazilian children, CRF was only positively associated with Math in girls [41], while in another study in Chilean children it was negatively related to reading/language arts and math scores in girls [42]. However, the higher CRF in boys than in girls could mediate this association.…”
Section: Discussionsupporting
confidence: 76%
“…The effect could not be explained by family income, parental education, genetic background, or past cognitive achievement and was robust to different measures of adiposity. Additionally, in preadolescents from Brazil, a negative association between skinfold thickness and performance in mathematics was reported to be significant in males, but not in females [ 55 ]. Our findings might be consistent with those of the literature showing that men bear a heavier burden following excessive weight gain.…”
Section: Discussionmentioning
confidence: 99%